Allograft failure in kidney transplant recipients who developed kidney failure secondary to ANCA‐associated vasculitis. Issue 4 (6th February 2021) - Kuhnel, Lukas; Hawley, Carmel M.; Johnson, David W.; Gobe, Glenda C.; Ellis, Robert J.; Francis, Ross S.
Abstract: Anti‐neutrophil cytoplasmic antibody (ANCA)–associated vasculitides are uncommon causes of kidney failure. In kidney transplant recipients who developed kidney failure secondary to ANCA‐associated vasculitis, disease recurrence is unlikely due to ongoing immunosuppression, and patients generally have good immunological outcomes. This study compared transplant outcomes between ANCA‐associated vasculitis and other etiologies of kidney disease. All 18 901 adult kidney transplant recipients (1990‐2018) were ascertained from the ANZDATA Registry. Cox proportional hazards models were used to compare allograft failure between etiologies of kidney disease. Of 254 participants whose primary disease was ANCA‐associated vasculitis, 95 (37%) developed allograft failure; of those who developed graft failure, 62 (65%) died with a functioning allograft. Compared with patients with IgA nephropathy, those with ANCA‐associated vasculitis had higher rates of all‐cause allograft failure (HR: 1.4, 95% CI: 1.2‐1.7); however, rates of death‐censored allograft failure were similar (HR: 1.0, 95% CI: 0.7‐1.4). The most frequent causes of death in the ANCA‐vasculitis group who died with a functioning graft were infection (23%) and malignancy (36%). Kidney transplant recipients who developed kidney failure secondary to ANCA‐associated vasculitis may have had a higher risk of dying due to complications of immunosuppression compared with most other causes of kidney failure; however, they also had lower risks of disease recurrence and rejection.